Artificial intelligence in soil microbiome analysis: a potential application in predicting and enhancing soil health—a review - Roberta Pace; Vincenzo Schiano Di Cola; Maurilia Maria Monti; Antonio Affinito; Salvatore Cuomo; Francesco Loreto; Michelina Ruocco (Discover Applied Sciences)
Abstract Soil is a depletable and non-renewable resource essential for food production, crop growth, and supporting ecosystem services, such as the retaining and cycling of various elements, including water. Therefore characterization and preservation of soil biological health is a key point for the development of sustainable agriculture. We conducted a comprehensive review of the use of Artificial Intelligence (AI) techniques to develop forecasting models based on soil microbiota data able to monitor and predict soil health. We also investigated the potentiality of AI-based Decision Support Systems (DSSs) for improving the use of microorganisms to enhance soil health and fertility. While available studies are limited, potential applications of AI seem relevant to develop predictive models for soil fertility, based on its biological properties and activities, and implement sustainable precision agriculture, safeguarding ecosystems, bolstering soil resilience, and ensuring the production of high-quality food.